Analisis Implementasi Pernyataan Standar Akuntansi Keuangan 109 Tentang Akuntansi Zakat Dan Infak/ Sedekah Pada Badan Amil Zakat Nasional Tapanuli Selatan - Choirunnisa Tri Ana Harahap (Journal of Islamic Economic and Business Studies, 2023)
PSAK No. 109 was made with the aim of accounting financial statements for zakat and infaq / alms transactions at ZIS fund management institutions. However, in practice, there are often discrepancies between the reports provided by ZIS fund and the standards set by IAI in PSAK No. 109. Thus this research is intended to determine the implementation of PSAK 109 carried out at BAZNAS South Tapanuli which is used for evaluation materials and empirical evidence on the management of ZIS funds in Indonesia. This research is qualitative research with a descriptive approach, which is a qualitative approach in this case is actually a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. The results showed that BAZNAS Tapanuli Selatan has not fully implemented PSAK 109 on Accounting for Zakat and Infaq / Alms where there is still information needed in PSAK 109 on Accounting for Zakat and Infaq / Alms but in the financial statements owned by BAZNAS Tapanuli Selatan it cannot be found. BAZNAS Tapanuli Selatan has provided the information needed in accordance with PSAK No. 109 but in the financial statements of BAZNAS Tapanuli Selatan it cannot be found.